The effect of intra-arterial angiotensin II on the hepatic tumor to non-tumor blood flow ratio for radioembolization: a systematic review. - Andor F van den Hoven (Public Library of Science (PLoS), 2014)
Purpose Treatment efficacy of intra-arterial radioembolization for liver tumors depends on the selective targeting of tumorous tissue. Recent investigations have demonstrated that tumors may receive inadequate doses of radioactivity after radioembolization, due to unfavorable tumor to non-tumor (T/N) uptake ratios of radioactive microspheres. Hepatic arterial infusion of the vasoconstrictor angiotensin II (AT-II) is reported to increase the T/N blood flow ratio. The purpose of this systematic review was to provide a comprehensive overview of the effect of hepatic arterial AT-II on T/N blood flow ratio in patients with hepatic malignancies, and determine its clinical value for radioembolization. Methods This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A structured search was performed in the PubMed, EMBASE and Cochrane databases. Only studies that presented data on T/N ratios before and after infusion of AT-II into the hepatic artery, in human patients with hepatic malignancies, were selected. Median T/N ratios before, during and after AT-II infusion, and the median T/N ratio improvement factor were extracted from the selected articles. All data on systemic blood pressure measurements and clinical symptoms were also extracted. Results The search identified 524 titles of which 5 studies, including a total of 71 patients were considered relevant. Median T/N ratios before infusion of AT-II ranged from 0.4 to 3.4. All studies observed a substantial improvement of the T/N ratio after AT-II infusion, with median improvement factors ranging from 1.8 to 3.1. A transitory increase of systemic blood pressure was observed during AT-II infusion. Conclusions Infusion of AT-II into the hepatic artery leads to an increase of the tumor to non-tumor blood flow ratio, as measured by T/N uptake ratios. Clinical trials are warranted to assess safety aspects, optimal administration strategy and impact on treatment efficacy during radioembolization.